Financial distress prediction in Nigerian oil and gas industry: a multivariate approach - Omolekan, O.; Ajayi, E.; Kazeem-Bayo, O.; Babalola, H. (Journal of Economic Research & Business Administration, 2022)
The oil and gas sector are in no doubt a very sensitive and equally a very important sector and majorly the main stay of Nigerian economy. Recent dropped in the prices of oil in the international market is of great concerned to all oil producing and exporting countries of which Nigeria is a major player. Colossal cost implications of collapsed business are enormous, detrimental, anti-economic growth and development but preventable if the early warning distress signals can be predicted. Thus, this study predicts financial distress in Nigeria oil and gas firms using multivariate approach. Longitudinal design was adopted for the study. Data were extracted from Nigeria Stock Exchange (NSE) fact books from year 2000 to 2018. Information obtained were arranged and collated in ratio analysis. Multiple discriminant analysis (MDA) was used to predict the early warning signals and post-prediction differences were tested using t-test. The prediction results revealed the failure early warning signals in the study area to be earning before interest and tax (EBIT), working capital (WCA), and TAR with strong prediction accuracy. The study concluded that Nigerian oil and gas companies are susceptible to failure given the early warning signals identified. It is recommended that the sampled firms should take into cognizance the identified early warning signals to prevent financial distress and take preventive measures towards rejuvenation. Key words: Early warning signals, financial distress prediction, MDA, oil and gas firms, rejuvenation.